PENGGUNAAN MODEL CONCEPT SENTENCE DALAM PEMBELAJARAN MENULIS PARAGRAF - Suhartini Suhartini; Suhardi Abdullah; Pamuti Pamuti (Universitas Khairun, 2019)
The objectives of these research was to developed student’s competence of writing a paragraph in using Concept sentence. These Classroom action research held at the 3rd grade of SDN 20 West Halmahera at the year of 2018-2019. The type of this research was classroom action research and consist of two cycles that includes in planning, action, observation and reflection. The technique that used in this research were, observation, interviews and evaluation. The result of this researched concluded that in using concept sentence increased students competence in writing a paragraph proved by some items consisted of (1) concept sentence correctly implemented (2) the setting or placement of the punctuation and letter were correctly (3) the students chosen of words in thir thought based on the key words (4) the interrelation of each sentence in a paragraph was correctly design.Key Words: Improving, concept sentence model, writing paragraph